2010
DOI: 10.1088/0957-0233/21/2/025308
|View full text |Cite
|
Sign up to set email alerts
|

Measuring a narrow Bessel beam spot by scanning a charge-coupled device (CCD) pixel

Abstract: By scanning a charge-coupled device (CCD) camera transverse to the beam axis and observing the variation in counts on a marked pixel, we demonstrate that we can measure a laser beam spot size smaller than the size of the CCD-pixel. We find this method particularly attractive for measuring the size of central spot of a Bessel beam, for which the established scanning knife-edge method does not work appropriately because of the large contribution of the rings surrounding the central spot to the signal.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Charge-coupled device (CCD) cameras are widely used to measure laser beam quality parameter. 18,19 We find that when the laser beam is directly irradiated on the photosensitive surface of the industrial camera, the photosensitive element will go beyond the linear region and become saturated, and the laser facula area cannot be measured accurately.…”
Section: Experiments Theory and Methodsmentioning
confidence: 94%
“…Charge-coupled device (CCD) cameras are widely used to measure laser beam quality parameter. 18,19 We find that when the laser beam is directly irradiated on the photosensitive surface of the industrial camera, the photosensitive element will go beyond the linear region and become saturated, and the laser facula area cannot be measured accurately.…”
Section: Experiments Theory and Methodsmentioning
confidence: 94%
“…However, such a small change is difficult to sense in our setup as resolution of our CCD is ∼6.45 μm (size of a pixel). Nevertheless, such a small variation in Bessel-beam spot size can be measured by other more accurate methods [16].…”
Section: A Variation Of Fwhm With Axicon Mirror Separation (D )mentioning
confidence: 99%
“…As FWHM is varying linearly with focal length f , the spot size of the generated Bessel beam can be further reduced if a lens of smaller focal length is used. We have earlier demonstrated the generation of a Bessel beam of FWHM smaller than the size of a CCD pixel by using a shorter focal length lens [16]. Thus the range over which the spot size can be varied by varying separation d can be further extended by replacing the lens in the setup.…”
Section: A Variation Of Fwhm With Axicon Mirror Separation (D )mentioning
confidence: 99%
See 1 more Smart Citation
“…This confirms a change in the size of the beam which is noticeable when comparing each of the frames in both figures. It has been shown that an accurate measurement of the size of the central spot can be achieved by scanning the position of the charged coupled device pixel [20].…”
Section: Generation Of Bessel-like Beams (Blbs)mentioning
confidence: 99%